Особливості застосування змістовних теорій мотивування працівників в умовах воєнного стану - Пшик-Ковальська, О. О.; Гадик, В. О.; Pshyk-Kovalska, O. O.; Hadyk, V. O. (Видавництво Львівської політехніки, 2024)
У статті розглянуто актуальні питання мотивування персоналу на українських підприємствах у контексті зовнішніх викликів, спричинених кризою та воєнним станом в Україні. Проаналізовано основні змістовні теорії мотивування, особливу увагу присвя- чено адаптації цих теорій до сучасних умов функціонування підприємства, тому зроб- лено акцент на забезпеченні первинних потреб працівників. Автори запропонували ре- комендації для вибору ефективного мотиваційного підходу в умовах воєнного кон- флікту.

The article examines the intricacies of staff motivation at Ukrainian enterprises in the conditions of unprecedented challenges associated with the ongoing crisis and martial law. Modern motivation strategies, aimed at identifying and satisfying actual needs, should contribute to the formation of conditions that provide staff with a sense of stability and security, thereby contributing to an increase in their productivity and satisfaction at the workplace. By studying the main theories of motivation, such as Abraham Maslow’s hierarchy of needs, the theory Alderfer’s ERG, McClelland’s acquired needs theory, and Herzberg’s two-factor theory, the authors highlight the multifaceted implications of each perspective, especially as applied to the unique context of wartime. The scholarly study begins with a comprehensive analysis of motivation theories, providing readers with a detailed understanding of their applicability and challenges in various contexts. The article outlines Maslow’s hierarchical progression of needs as opposed to her more variable Alderfer classification. The researchers proposed A. Maslow’s Adapted Pyramid of Needs for motivating employees in martial law conditions, which, when used effectively, will help managers create the necessary psycho-emotional environment and minimize staff turnover. In addition, David McClelland’s emphasis on achievement, affiliation, and power needs, which are not the priority desires of employees compared to safety needs, is explored in detail. Herzberg’s dichotomy between hygiene and motivational factors is also described, which gives insight into the importance of balancing the satisfaction of hygiene and motivating needs. This article highlights the renewed relevance of foundational motivational theories in shaping pragmatic strategies in a changing business landscape. In particular, Maslow’s hierarchy and Herzberg’s two-factor theory become the main guidelines for the development of effective motivational interventions, especially taking into account the urgent needs of employees, such as physiological and safety requirements, which are the most important in the modern Ukrainian environment. The authors of the article give examples of specific measures that Ukrainian enterprises can take. use to increase the motivation of personnel in wartime conditions. In particular, intangible incentives such as support, team building, volunteering, extra days off and vacations are effective. At the end of the article, the importance of understanding and adapting motivation theories to the specific context of Ukrainian enterprises during the war is emphasized. By recognizing the nuances of their workforce’s needs, managers can effectively implement motivational strategies that promote employee engagement, productivity, and resilience in the face of conflict.
Features of the application of substantial theories of employee motivation in the conditions of the state of martial
Keywords: мотивування; змістовні теорії мотивування; воєнний стан; пер- винні потреби; вторинні потреби; матеріальне стимулювання; нематеріальне стимулю- вання; продуктивність праці; motivation; substantive theories of motivation; martial law; primary needs; secondary needs; material stimulation; non-material stimulation; productivity; 331.1